Adaptation of the method for identification and quantification of mono- and diacylglycerols in vegetable oils - D. D. Zhdanov; E. A. Butina; I. A. Dubrovskaya; E. O. Gerasimenko; A. Y. Shazzo (Новые технологии, 2024)
The article presents the research on the adaptation and implementation of a method for determining mono- and diacylglycerols in vegetable oils. The relevance of the research is determined by the introduction of standardization of monochloropropanediols and glycidol in vegetable oils and some types of fat and oil products since 2025. According to the scientific literature, mono- and diacylglycerols, formed during the ripening of oil seeds under the influence of the enzyme lipase, are precursors of monochloropropanediols and glycidol, which, in turn, according to the World Health Organization, are carcinogenic substances. Some of the most probable mechanisms for the formation of contaminants from mono- and diacylglycerols have been considered; according to them diacylglycerols are considered to be the main source of glycidyl ethers, and monoacylglycerols  are that of  monochloropropanediols. An important factor influencing the speed and completeness of the described reactions is the presence in the system of water molecules, chlorine ions, hydrogen protons, as well as high temperatures. Catalysts for such side reactions are heavy metals, including their salts. Thus, in order to implement effective measures to control the formation of contaminants in oil, it is important to have a complete picture of the quality indicators of the feedstock and, above all, data on the content of mono- and diacylglycerols, methods for determining which are not available in laboratory practice in the Russian Federation.The goal of the research is to develop a method for the quantitative determination of mono- and diacylglycerols in vegetable oils.As a result of the research, the sample preparation method has been improved, calibration dependencies have been determined using an internal standard, and an identification and quantitative analysis technique has been proposed, on the basis of gas chromatography with a flame ionization detector and the use of a high-temperature capillary column. Verification work has been carried out and the metrological characteristics of the proposed method have been determined. The method has been tested on real objects – various types of vegetable oils.